2005
DOI: 10.1139/v05-214
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation pathways of negative ions produced by electrospray ionization of acyclic dicarboxylic acids and derivatives

Abstract: Fragmentation pathways have been studied on the monoanions formed during electrospray ionization of a wide range of aliphatic dicarboxylic acids and their monoesters. All negative ion spectra were obtained from alcoholic or aqueous methanolic solutions without buffers or adjustment of pH, using either a Finnigan LCQ ion trap or a VG-Micromass Quattro triple quadrupole mass spectrometer. Fragmentation pathways were studied using collision-induced dissociation and isotopic-labelling techniques. Two primary fragm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 35 publications
4
51
2
Order By: Relevance
“…In the present study, the unanticipated loss of HONO observed upon CID of deprotonated Ns amino acids differed from the documented fragmentation behavior of other sulfonamide and carboxylate ions. The collection of functional groups in the Ns derivative of glycine (NsGly) also enabled three other distinct fragmentation pathways of deprotonated NsGly to be observed, indicative of a rich gas‐phase chemistry for multifunctional anions.…”
Section: Introductioncontrasting
confidence: 72%
“…In the present study, the unanticipated loss of HONO observed upon CID of deprotonated Ns amino acids differed from the documented fragmentation behavior of other sulfonamide and carboxylate ions. The collection of functional groups in the Ns derivative of glycine (NsGly) also enabled three other distinct fragmentation pathways of deprotonated NsGly to be observed, indicative of a rich gas‐phase chemistry for multifunctional anions.…”
Section: Introductioncontrasting
confidence: 72%
“…2), as suggested by Kirkup and Mulholland (2004). This is due to the formation of dimers and aggregates with water during ESI, especially at higher concentrations, and possibly varying fragmentation (Grossert et al, 2005) at different concentration levels. Limits of detection (expressed in ng) have been defined from the calibration curves and converted to ng m −3 according to the experimental sampling flows of WEDD and AC for each experiment.…”
Section: Ion Chromatography Systemmentioning
confidence: 83%
“…dehydration (m/z 167) and decarboxylation (m/z 141) of pinic acid and dehydration of hydroxypinonic acid (m/z 181). This fragmentation pattern is significant for dicarboxylic acids (Grossert et al, 2005) in general. The MS 3 -spectra of the daughter ion with m/z 185 of m/z 367 (Fig.…”
Section: α-Pinene Ozonolysismentioning
confidence: 89%
“…The intensity seems to be dependent on the molecular weight of the hydroxyl component or the ratio of molecular weights of hydroxyl and dicarboxylic acid component in the ester molecules. Furthermore, always visible in the MS/MS-spectra are low intensities of fragments from losses of water, carbon dioxide and combined losses of water and carbon dioxide of the dicarboxylic acid, which is typical for dicarboxylic acids of different chain length (Grossert et al, 2005). The MS 3 -spectrum of the m/z 131 fragment ion (Fig.…”
Section: Cyclohexene Ozonolysismentioning
confidence: 91%